The juridification of business ethics - Jansen, Bart (Cham : Springer, 2023)
This book provides a theory of the juridification of business ethics. Ethical codes pop up everywhere in the business world and increasingly resemble the code of law. A focus on compliance rather than reflection becomes the norm. Legal perspectives replace ethical perspectives, turning ethicists into lawyers without a law degree. This juridification of business ethics conceals a diminishing trust in ethics, as legal reasoning substitutes philosophical thinking. By appealing to the critical study of law, Bart Jansen advocates for a renewed focus on the ethical side of business. This book shows the importance of a good balance between law and ethics in business and is of great interest to both academics and professionals
1. Introduction -- 2. The Camera Iuridica -- 3. The Juridical Disclosure of Ethics in the Netherlands and Indonesia -- 4. Ethics as the Regulation of the Self -- 5. Dispute Resolution as an Ethical Phantasm -- 6. New Materialism in Business Ethics -- 7. Business Ethics on Its Last Legs.-- 8. Conclusions and Final Remarks -- References -- Index.
BIBINDX
Keywords: Commercial law -- Moral and ethical aspects; Business ethics